CGIAR at SB62: Influencing Global Climate Policies with Science-Based Advocacy - Edward-Uwadiale, Regina; Miranda, Daniela; Mukherji, Aditi; Villarino, Eliza; Njuguna, Lucy (2025)
As the United Nations Framework Convention on Climate Change (UNFCCC) 62nd Subsidiary Body for Scientific and Technological Advice (SBSTA) and Subsidiary Body for Implementation (SBI) negotiations (SB62) convene in Bonn in June 2025, CGIAR is gearing up to advocate that food and agriculture are front and center in global climate policy discussions. These mid-year talks set the stage for outcomes at COP30 in Brazil later this year. In line with its mission, CGIAR will contribute scientific evidence, policy insights and collaboration across key negotiation tracks – from climate finance and adaptation goals to agriculture and just transitions. Agriculture and food systems, which account for roughly one-third of global greenhouse gas emissions, have historically received only 4.3% of global climate finance. CGIAR is working to close this gap through its contributions to influence global climate policy.